The resilience of tradition: Malay allusions in contemporary architecture - Jahn Kassim, Puteri Shireen; Mohd Nawawi, Norwina; Abdul Majid, Noor Hanita (Areca Books, 2017)
How and to what extend is contemporary Malaysian architecture influenced by Malay culture, values and forms? In what way is the Malay Modern situated within the discourse of contemporary tropical architecture? Can the evolution of Malay architecture answer the challenge of developing climatically appropriate eco-architecture? Such questions are being asked in Malaysian Universities and in international conferences looking at modernism, postmodernism, regionalism, tropical architecture, green building, and sustainability. Malay vernacular architecture is intrinsically environmentally-conscious, embodying sustainable principles, design ideas, and tectonic solutions. Globally, there is growing awareness that culturally -responsive strategies in architecture can be aligned with advancing sustainability standards in buildings and contemporary urban development. This book compiles attempts by architects and builders so far to respond to two critical agendas-the sustainability agenda and the cultural agenda. In the era of climate change, the challenge facing building professionals and designers in Malaysian and Asian cities is how to develop and expand sustainability strategies which are culturally rooted in local genius and regional identity.